Antinociceptive and Anti-Inflammatory Activities of the Ethanolic Extract from Synadenium umbellatum Pax. (Euphorbiaceae) Leaves and Its Fractions. (21st January 2013) - Borges, Rodrigo; Nascimento, Marcus Vinícius Mariano; de Carvalho, Adryano Augustto Valladão; Valadares, Marize Campos; de Paula, José Realino; Costa, Elson Alves; da Cunha, Luiz Carlos
Abstract : Synadenium umbellatum Pax., popularly known in Brazil as "cola-nota, " "avelós, " "cancerola, " and "milagrosa", is a plant species used in folk medicine for the treatment of inflammation, pain, and several diseases. This study aimed to investigate the antinociceptive and anti-inflammatory activities of the ethanolic extract from Synadenium umbellatum Pax. leaves (EES) and its hexane (HF), chloroform (CF), and methanol/water (MF) fractions using the acetic acid-induced abdominal writhing test, formalin-induced paw licking test, tail flick test, croton oil-induced ear edema test, and carrageenan-induced peritonitis test. EES and MF reduced the number of acetic acid-induced abdominal writhes, while CF and HF did not. EES effect on acetic acid-induced abdominal writhing was reversed with a pretreatment with naloxone. EES reduced licking time in both phases of the formalin-induced paw licking test, but did not prolong the latency in the tail flick test. These results show that EES presented antinociceptive activity, probably involving the opioid system, anti-inflammatory activity in the croton oil-induced ear edema test, and leukocyte migration into the intraperitoneal cavity. MF also presented anti-inflammatory activity in the croton oil-induced ear edema test. In conclusion, EES and MF have antinociceptive activity involving the opioid system and anti-inflammatory activity.